Potensi Sumber Energi di Indonesia: Tantangan dan Peluang - Marwan Effendy (PROSIDING SEMINAR NASIONAL LPPM UMP, 2021)
Energy is a vital source for human life and activities. The availibility of clean and environmentally friendly energy is a necessity to ensure a healthy and comfortable life. The integration of secondary energy sources and storage technologies for adaptive energy systems is very beneficial in the future.